Analysis of trp repressor-operator interaction by filter binding. - Klig, L S (1987)
A filter binding assay was developed that allows measurement of specific binding of trp repressor to operator DNA. The most important feature of this procedure is the concentration and type of salt present in the binding buffer. Using this assay the dissociation constant of the repressor-operator complex was determined to be 2.6 X 10(-9) M, and 1.34 repressor dimers were found to be bound to each operator-containing DNA molecule. These values agree with those obtained by more complex methods. The dissociation constant of the repressor for the corepressor L-tryptophan in the presence of operator DNA was shown to be 2.5 X 10(-5) M. A synthetic 48 bp operator fragment was used to determine the repressor-operator dissociation constant in the presence of tryptophan or tryptophan analogs which have higher or lower affinities for aporepressor. The rate of dissociation of repressor from operator DNA also was determined. Our findings indicate that dissociation is influenced by the concentration of tryptophan or tryptophan analogs and suggest that release of the corepressor may be the first step in dissociation of the repressor-operator complex.